Palestine in Indonesian foreign policy: The relevance of Soekarno's speech at the 1955 AAC - Sopian Suprianto; Asep Achmad Hidayat; Usman Supendi (UIN Sunan Gunung Djati Bandung, 2026)
The Palestinian issue is one of the most complex conflicts in contemporary global politics, reflecting systemic injustice and the failure of international institutions to uphold human rights and national sovereignty. As a country born from the decolonization struggle, Indonesia has consistently voiced support for Palestinian independence, both through diplomatic, humanitarian, and international forums. This article reveals that President Soekarno's speech at the 1955 Asia-Africa Conference (AAC) was not just a symbolic statement, but became the ideological and moral foundation for Indonesia's foreign policy towards Palestine. Through a qualitative approach with a historical-diplomatic method, this article analyzes the content of Soekarno's speech, KAA documents, and the practice of Indonesian diplomacy from the early era of independence to the post-Reformation period. This research demonstrates that the values of anti-colonialism, South-South solidarity, and global justice, as conveyed by Soekarno, remain the foundation of Indonesia's stance towards Palestine to this day. The scientific contribution of this study lies in strengthening the post-colonial perspective in the study of Indonesian diplomacy and affirming the importance of ideological heritage in shaping the direction of value-based foreign policy.